Climate change: a review of its health impact and percieved awareness by the young citizens - Rahman, Muhammad Sabbir; Mohamad, Osman; Abu Zarim, Zainal (Canadian Center of Science and Education, 2014)
In recent time climate change and its impact on human health and awareness constitute a set of complex and serious consequences to be tackled by an individual country. Climate change is not merely an environmental issue, but also it is a threat that goes beyond national borders. The purpose of this study is to identify the awareness and the impact of climate change, perceived by the young citizens in Malaysia by focusing on gender differences. Based on a survey of 200 respondents from different public and private University's students in Malaysia, this research used descriptive statistics and T-test to look into the research objective. The results revealed media can play an important role in the awareness of climate change. Meanwhile the male respondents have shown considerable attention on the physical impact of climate change like heat related stress. On the other hand female respondents have shown considerable attention to the psychological impact by the climate change. From a pragmatic perspective, the findings from this research will assists the policy makers to understand more about the perceived awareness on the climate change issues of the young citizens which ultimately assist them to inaugurate new initiatives to confront the challenges of climate changes. This research is among the pioneer study on the issue of the perceived awareness in regards to climate change in Malaysia by focusing on gender differences.